Investigation of the role of histamine in antigen-induced bronchoconstriction in the ascaris-hypersensitive dog. - Krell, R D (1978)
1 Aerosol administration of ascaris antigen to the airways of ascaris-hypersensitive dogs provoked increases in pulmonary resistance (Rp) and decreases in dynamic lung compliance (Cdyn). These changes in pulmonary mechanics were not inhibited by the histamine H1-receptor antagonists, diphenhydramine or mepyramine. 2 Increases in Rp and decreases in Cdyn induced by a histamine aerosol were markedly or totally inhibited by comparable doses of these H1-antihistamines. 3 Doses of antigen which produced pathophysiological pulmonary responses failed to produce a detectable histamine release from the cardiopulmonary system in vivo. Aerosol antigen provocation, equivalent to 5 to 9 times greater than that which produced substantial pathophysiological pulmonary responses, did cause histamine release in vivo. 4 The canine cardiopulmonary system showed only a modest ability to remove and/or degrade circulating histamine. 5 It is concluded that histamine may not play a major role in mediating the acute antigen-induced bronchoconstriction in the ascaris-hypersensitive dog.